INFLUENCE OF LIFT FORCE ON METHANE BURNING IN THE COMBUSTION CHAMBER - Bolegenova, S.А. (Recent Contributions to Physics, 2018)
The numerical solution of the problem of turbulent combustion of methane in the flat burner has been obtained. The influence of lift force and the initial level of turbulence on the averaged, pulsation characteristics of the diffusion torch has been researched.